The role of botulinum toxin in the treatment of diseases beyond aesthetics: migraine, hyperhidrosis and bruxism - literature review - Oskroba, Karolina; Sokołowski, Maciej; Graczyk, Estera; Kryślak, Joanna; Skibicka, Katarzyna; Solarz, Adam; Szabelski, Szymon; Cwalina, Oliwia; Turcza , Jakub Filip (Quality in Sport, 2025)
In the 19th century, botulinum toxin was recognized solely as a poison. Subsequent research led to its medical applications, and today, it is predominantly utilized in aesthetic medicine. However, its therapeutic potential extends beyond cosmetic procedures. This review examines the use of botulinum toxin in the management of migraine, bruxism, and hyperhidrosis. In these conditions, botulinum toxin primarily serves as a symptomatic treatment, often considered when first-line therapies fail. To provide a comprehensive understanding, this article discusses the pathophysiology of these disorders, standard treatment protocols, and the mechanisms by which botulinum toxin alleviates symptoms. Guidelines from scientific societies regarding injection frequency and anatomical sites are outlined. Additionally, the type of botulinum toxin, dosage, treatment costs, potential adverse effects, and challenges related to treatment durability are reviewed. Further research on botulinum toxin is warranted, as the therapy is associated with high costs and necessitates multiple injections in close succession. To improve accessibility, therapeutic protocols that reduce the number of injections should be developed, or formulations with an extended duration of action should be introduced.